Characteristics of Soil Active Carbon Fractions and Carbon Pool Stability in Major Forest Types in Northern Daxing’an Mountains - LIU Beibei; CAI Tijiu (Shuitu Baochi Xuebao)
[Objective] Soil organic carbon is an important component of the carbon cycle in forest ecosystems, and active organic carbon can indicate changes in soil carbon pools. Studying the pattern of change of soil active carbon fractions and carbon pool stability in different forest types is of great significance to the understanding of the biogeochemical processes of the carbon cycle, and can provide a basis for the management of ecosystem carbon pools oriented to carbon sequestration and emission reduction. [Methods] The soil samples of 0-10 and 10-20 cm soil layers were collected from May to September in the growing season from Larix gmelinii, Pinus sylvestris var. mongolica, Betula platyphylla and Populus davidiana forests in the northern part of Daxing’ anling, and the contents of different reactive carbon oxides in the soils were measured by the modified Loginow method, and the active carbon utilisation (ER) and carbon pool activity (CPA) were used to measure the carbon pool stability and the carbon cycle. [Results] (1) From May to September, soil total organic carbon (TOC), highly active organic carbon (LOC-H) and moderately active organic carbon (LOC-M) of the four forest types showed a “single-peak” trend of change, and reached a peak in August, and the contents were higher in broad-leaved forests than in coniferous forests. (2) The utilisation rate of soil stability organic carbon (ER4) fluctuated between 72.33% and 85.11% from May to September, it was significantly higher than the utilisation rates of the other three types of active carbon, and dominated the soil carbon pool. (3) Soil carbon pool activity (CPA) fluctuated between 0.20 and 0.38, with P. davidiana forests>B. platyphylla forests>P. sylvestris var. mongolica forests >L. gmelinii forests; that of coniferous forests peaked in August, while that of broad-leaved forests were highest in May. (4) Soil active organic carbon content and carbon pool stability were subject to the combined effects of climatic factors and soil factors. Sucrase was the main influence of soil factors, while rainfall and photosynthetically active radiation were more influential among climatic factors. The overall stability of soil organic carbon in coniferous forests in the cold temperate zone was greater than that in broad-leaved forests, but the rate of organic carbon loss from deeper soil layers in coniferous forests was higher than that in broad-leaved forests under higher temperatures. [Conclusion] This study helps to improve the understanding of soil active carbon and organic carbon pools in cold temperate forests, artificially promoting secondary forest succession or introducing coniferous species as soon as possible is suggested to form mixed forests in the region, but the role played by broad-leaved forests in soil carbon pools should not be ignored in the context of increasing global warming.